2021
DOI: 10.21608/ijma.2021.38601.1170
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Modified Alvarado Score and Abdominal Ultrasound Diagnostic Value of Acute Appendicitis in Children

Abstract: Background: Diagnosis of acute appendicitis depends mainly on clinical diagnosis. However, the high negative rate remains a challenge and different aids for diagnosis had been proposed. The aim of the work: The current work aimed to assess the sensitivity of Modified Alvarado Score [MAS] in diagnosis of acute appendicitis. Patients and Methods: One hundred children with clinical manifestations of acute appendicitis were included. Patients were categorized into two groups according to MAS: [group A] included 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Furthermore, the present study in consistent with Rizk et al (1) who illustrated that the sensitivity of Modified Alvarado score was (96.0%) while the sensitivity of ultrasound (89.4%). In contrast, our results in disagreement with Kansakar et al (18) who demonstrated that ultrasound had higher sensitivity (74.19%) and accuracy (75.0 %) as compared to Modified Alvarado score for diagnosis of appendicitis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the present study in consistent with Rizk et al (1) who illustrated that the sensitivity of Modified Alvarado score was (96.0%) while the sensitivity of ultrasound (89.4%). In contrast, our results in disagreement with Kansakar et al (18) who demonstrated that ultrasound had higher sensitivity (74.19%) and accuracy (75.0 %) as compared to Modified Alvarado score for diagnosis of appendicitis.…”
Section: Discussionsupporting
confidence: 92%
“…It includes neutrophilic infiltration of the muscularis propria. This confirms the clinical pre-operative diagnosis and exclude missed one (1) .…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations